Antigen-dependent modulation of immune responses to antigen-Fc fusion proteins by Fc-effector functions - Richel, Elie; Wagner, Jannik; Klessing, Stephan; Di Vincenzo, Riccardo; Temchura, Vladimir; Überla, Klaus (Frontiers in Immunology, 2023)
Background: Fc-fusion proteins have been successfully developed for therapeutic purposes, but are also a promising platform for the fast generation and purification of immunogens capable of inducing strong humoral immune responses in preclinical immunization studies. As the Fc-portion of immunoglobulins fused to an antigen confers functional properties of the parental antibody, such as dimerization, binding to Fc-receptors and complement activation, several studies reported that Fc-fusion proteins elicit stronger antigen-specific antibody responses than the unfused antigen. However, dimerization or half-life extension of an antigen have also been described to enhance immunogenicity. Methods: To explore the role of Fc-effector functions for the immunogenicity of fusions proteins of viral glycoproteins and Fc fragments, the HIV-1 gp120 and the RBD of SARS-CoV-2 were fused to the wild type muIgG2a Fc fragment or mutants with impaired (LALA-PG) or improved (GASDIE) Fc-effector functions. Results: Immunization of BALB/c mice with DNA vaccines encoding gp120 – Fc LALA-PG induced significantly higher antigen-specific antibody responses than gp120 – Fc WT and GASDIE. In contrast, immunization with DNA vaccines encoding the RBD fused to the same Fc mutants, resulted in comparable anti-RBD antibody levels and similar neutralization activity against several SARS-CoV-2 variants. Conclusion: Depending on the antigen, Fc-effector functions either do not modulate or suppress the immunogenicity of DNA vaccines encoding Fc-antigen fusion proteins.
CRIS-Team Scopus Importer:2023-11-03
Keywords: DNA immunization; Fc-effector functions; Fc-fusion proteins; HIV; mice; SARS-CoV-2

Covalent coupling of HIV-1 glycoprotein trimers to biodegradable calcium phosphate nanoparticles via genetically encoded aldehyde-tags - Damm, Dominik; Kostka, K.; Weingärtner, Christoph; Wagner, Jannik; Rojas-Sánchez, L.; Gensberger-Reigl, Sabrina; Sokolova, V.; Überla, Klaus; Epple, M.; Temchura, Vladimir (Acta Biomaterialia, 2022)
The usage of antigen-functionalized nanoparticles has become a major focus in the field of experimental HIV-1 vaccine research during the last decade. Various molecular mechanisms to couple native-like trimers of the HIV-1 envelope protein (Env) onto nanoparticle surfaces have been reported, but many come with disadvantages regarding the coupling efficiency and stability. In this study, a short amino acid sequence (“aldehyde-tag”) was introduced at the C-terminus of a conformationally stabilized native-like Env. The post-translational conversion of a tag-associated cysteine to formylglycine creates a site-specific aldehyde group without alteration of the Env antigenicity. This aldehyde group was further utilized for bioconjugation of Env trimers. We demonstrated that the low acidic environment necessary for this bioconjugation is not affecting the trimer conformation. Furthermore, we developed a two-step coupling method for pH-sensitive nanoparticles. To this end, we conjugated aldehyde-tagged Env with Propargyl-PEG3-aminooxy linker (oxime ligation; Step-one) and coupled these conjugates by copper-catalyzed azide-alkyne cycloaddition (Click reaction; Step-two) to calcium phosphate nanoparticles (CaPs) functionalized with terminal azide groups. CaPs displaying orthogonally arranged Env trimers on their surface (o-CaPs) were superior in activation of Env-specific B-cells (in vitro) and induction of Env-specific antibody responses (in vivo) compared to CaPs with Env trimers coupled in a randomly oriented manner. Taken together, we present a reliable method for the site-specific, covalent coupling of HIV-1 Env native-like trimers to the surface of nanoparticle delivery systems. This method can be broadly applied for functionalization of nanoparticle platforms with conformationally stabilized candidate antigens for both vaccination and diagnostic approaches. Statement of significance: During the last decade antigen-functionalized nanoparticles have become a major focus in the field of experimental HIV-1 vaccines. Rational design led to the production of conformationally stabilized HIV-1 envelope protein (Env) trimers - the only target for the humoral immune system. Various molecular mechanisms to couple Env trimers onto nanoparticle surfaces have been reported, but many come with disadvantages regarding the coupling efficiency and stability. In this paper, we describe a highly selective bio-conjugation of Env trimers to the surface of medically relevant calcium phosphate nanoparticles. This method maintains the native-like protein conformation and has a broad potential application in functionalization of nanoparticle platforms with stabilized candidate antigens (including stabilized spike proteins of coronaviruses) for both vaccination and diagnostic approaches.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Aldehyde-tag; Calcium phosphate nanoparticles; HIV-1 Env native-like trimers; Orthogonal; Site-specific coupling; Surface conjugation

Design and Functional Characterization of HIV-1 Envelope Protein-Coupled T Helper Liposomes - Damm, Dominik; Suleiman, Ehsan; Theobald, Hannah; Wagner, Jannik; Batzoni, Mirjam; Kohlhauser, Bianca Ahlfeld Née; Walkenfort, Bernd; Albrecht, Jens Christian; Ingale, Jidnyasa; Yang, Lifei; Hasenberg, Mike; Wyatt, Richard T.; et al. (Pharmaceutics, 2022)
Functionalization of experimental HIV-1 virus-like particle vaccines with heterologous T helper epitopes (T helper VLPs) can modulate the humoral immune response via intrastructural help (ISH). Current advances in the conjugation of native-like HIV-1 envelope trimers (Env) onto liposomes and encapsulation of peptide epitopes into these nanoparticles renders this GMP-scalable liposomal platform a feasible alternative to VLP-based vaccines. In this study, we designed and analyzed customizable Env-conjugated T helper liposomes. First, we passively encapsulated T helper peptides into a well-characterized liposome formulation displaying a dense array of Env trimers on the surface. We confirmed the closed pre-fusion state of the coupled Env trimers by immunogold staining with conformation-specific antibodies. These peptide-loaded Env-liposome conjugates efficiently activated Env-specific B cells, which further induced proliferation of CD4+ T cells by presentation of liposome-derived peptides on MHC-II molecules. The peptide encapsulation process was then quantitatively improved by an electrostatically driven approach using an overall anionic lipid formulation. We demonstrated that peptides delivered by liposomes were presented by DCs in secondary lymphoid organs after intramuscular immunization of mice. UFO (uncleaved prefusion optimized) Env trimers were covalently coupled to peptide-loaded anionic liposomes by His-tag/NTA(Ni) interactions and EDC/Sulfo-NHS crosslinking. EM imaging revealed a moderately dense array of well-folded Env trimers on the liposomal surface. The conformation was verified by liposomal surface FACS. Furthermore, anionic Env-coupled T helper liposomes effectively induced Env-specific B cell activation and proliferation in a comparable range to T helper VLPs. Taken together, we demonstrated that T helper VLPs can be substituted with customizable and GMP-scalable liposomal nanoparticles as a perspective for future preclinical and clinical HIV vaccine applications. The functional nanoparticle characterization assays shown in this study can be applied to other systems of synthetic nanoparticles delivering antigens derived from various pathogens.
CRIS-Team Scopus Importer:2022-07-15
Keywords: coupling mechanism; Env trimer; functionalization; GMP; HIV; immunogold staining; intrastructural help; peptide encapsulation; T helper liposomes; vaccine

Immunogenicity of Recombinant Lipid-Based Nanoparticle Vaccines: Danger Signal vs. Helping Hand - Temchura, Vladimir; Wagner, Jannik; Damm, Dominik (Pharmaceutics, 2024)
Infectious diseases are a predominant problem in human health. While the incidence of many pathogenic infections is controlled by vaccines, some pathogens still pose a challenging task for vaccine researchers. In order to face these challenges, the field of vaccine development has changed tremendously over the last few years. For non-replicating recombinant antigens, novel vaccine delivery systems that attempt to increase the immunogenicity by mimicking structural properties of pathogens are already approved for clinical applications. Lipid-based nanoparticles (LbNPs) of different natures are vesicles made of lipid layers with aqueous cavities, which may carry antigens and other biomolecules either displayed on the surface or encapsulated in the cavity. However, the efficacy profile of recombinant LbNP vaccines is not as high as that of live-attenuated ones. This review gives a compendious picture of two approaches that affect the immunogenicity of recombinant LbNP vaccines: (i) the incorporation of immunostimulatory agents and (ii) the utilization of pre-existing or promiscuous cellular immunity, which might be beneficial for the development of tailored prophylactic and therapeutic LbNP vaccine candidates.
CRIS-Team Scopus Importer:2024-02-02
Keywords: adjuvants; cellular immunity; heterologous T cell help; immunogenicity; intrastructural help; lipid-based nanoparticles; liposomes; Toll-like receptor ligand; universal T cell epitope; vaccine antigen

Influence of AAV vector tropism on long-term expression and Fc-γ receptor binding of an antibody targeting SARS-CoV-2 - Wagner, Jannik; Müller-Schmucker, Sandra; Wang, Wenjun; Arnold, Philipp; Uhlig, Nadja; Issmail, Leila; Eberlein, Valentina; Damm, Dominik; Roshanbinfar, Kaveh; Enßer, Armin; Oltmanns, Friederike; Peter, Antonia Sophia; et al. (Communications Biology, 2024)
Long-acting passive immunization strategies are needed to protect immunosuppressed vulnerable groups from infectious diseases. To further explore this concept for COVID-19, we constructed Adeno-associated viral (AAV) vectors encoding the human variable regions of the SARS-CoV-2 neutralizing antibody, TRES6, fused to murine constant regions. An optimized vector construct was packaged in hepatotropic (AAV8) or myotropic (AAVMYO) AAV capsids and injected intravenously into syngeneic TRIANNI-mice. The highest TRES6 serum concentrations (511 µg/ml) were detected 24 weeks after injection of the myotropic vector particles and mean TRES6 serum concentrations remained above 100 µg/ml for at least one year. Anti-drug antibodies or TRES6-specific T cells were not detectable. After injection of the AAV8 particles, vector mRNA was detected in the liver, while the AAVMYO particles led to high vector mRNA levels in the heart and skeletal muscle. The analysis of the Fc-glycosylation pattern of the TRES6 serum antibodies revealed critical differences between the capsids that coincided with different binding activities to murine Fc-γ-receptors. Concomitantly, the vector-based immune prophylaxis led to protection against SARS-CoV-2 infection in K18-hACE2 mice. High and long-lasting expression levels, absence of anti-drug antibodies and favourable Fc-γ-receptor binding activities warrant further exploration of myotropic AAV vector-based delivery of antibodies and other biologicals.
CRIS-Team Scopus Importer:2024-07-26

Modulation of immune responses to liposomal vaccines by intrastructural help - Damm, Dominik; Suleiman, Ehsan; Wagner, Jannik; Klessing, Stephan; Pfister, Felix; Elsayed, Hassan; Walkenfort, Bernd; Stobrawe, Jule; Mayer, Julia; Lehner, Elisabeth; Müller-Schmucker, Sandra; Hasenberg, Mike; et al. (European Journal of Pharmaceutics and Biopharmaceutics, 2023)
The encapsulation of HIV-unrelated T helper peptides into liposomal vaccines presenting trimers of the HIV-1 envelope glycoprotein (Env) on the surface (T helper liposomes) may recruit heterologous T cells to provide help for Env-specific B cells. This mechanism called intrastructural help can modulate the HIV-specific humoral immune response. In this study, we used cationic T helper liposomes to induce intrastructural help effects in a small animal model. The liposomes were functionalized with Env trimers by a tag-free approach designed to enable a simplified GMP production. The pre-fusion conformation of the conjugated Env trimers was verified by immunogold electron microscopy (EM) imaging and flow cytometry. The liposomes induced strong activation of Env-specific B cells in vitro. In comparison to previously established anionic liposomes, cationic T helper liposomes were superior in CD4+ T cell activation after uptake by dendritic cells. Moreover, the T helper liposomes were able to target Env-specific B cells in secondary lymphoid organs after intramuscular injection. We also observed efficient T helper cell activation and proliferation in co-cultures with Env-specific B cells in the presence of cationic T helper liposomes. Mouse immunization experiments with cationic T helper liposomes further revealed a modulation of the Env-specific IgG subtype distribution and enhancement of the longevity of antibody responses by ovalbumin- and Hepatitis B (HBV)-specific T cell help. Thus, clinical evaluation of the concept of intrastructural help seems warranted.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Env trimer; Functionalization; HIV vaccine; IgG subtype; Intrastructural help; Nanoparticle; Peptide encapsulation; T helper liposomes

Mucosal tumor vaccination delivering endogenous tumor antigens protects against pulmonary breast cancer metastases - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, Pascal; Viherlehto, Vera; Jörg, Leticia; Schmidt, Anna; Wagner, Jannik; Rückert, Michael; Flohr, Ann-Sophie; Geppert, Carol-Immanuel; Frey, Benjamin; Bayer, Wibke; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Generally, early-stage breast cancer has a good prognosis. However, if it spreads systemically, especially with pulmonary involvement, prospects worsen dramatically. Importantly, tumor-infiltrating T cells contribute to tumor control, particularly intratumoral T cells with a tissue-resident memory phenotype are associated with an improved clinical outcome. Methods Here, we use an adenoviral vector vaccine encoding endogenous tumor-associated antigens adjuvanted with interleukin-1β to induce tumor-specific tissue-resident memory T cells (TRM) in the lung for the prevention and treatment of pulmonary metastases in the murine 4T1 breast cancer model. Results The mucosal delivery of the vaccine was highly efficient in establishing tumor-specific TRM in the lung. Concomitantly, a single mucosal vaccination reduced the growth of pulmonary metastases and improved the survival in a prophylactic treatment. Vaccine-induced TRM contributed to these protective effects. In a therapeutic setting, the vaccination induced a pronounced T cell infiltration into metastases but resulted in only a minor restriction of the disease progression. However, in combination with stereotactic radiotherapy, the vaccine increased the survival time and rate of tumor-bearing mice. Conclusion In summary, our study demonstrates that mucosal vaccination is a promising strategy to harness the power of antitumor TRM and its potential combination with state-of-the-art treatments.
CRIS-Team Scopus Importer:2024-03-22

Propagation of SARS-CoV-2 in a Closed Cell Culture Device: Potential GMP Compatible Production Platform for Live-Attenuated Vaccine Candidates under BSL-3 Conditions? - Klessing, Stephan; Peter, Antonia Sophia; Fraedrich, Kirsten; Wagner, Jannik; Kummer, Mirko; Deutschmann, Janina; Steininger, Philipp; Steibl, Hans Dieter; Überla, Klaus (Viruses, 2023)
Live-attenuated SARS-CoV-2 vaccines present themselves as a promising approach for the induction of broad mucosal immunity. However, for initial safety assessment in clinical trials, virus production requires conditions meeting Good Manufacturing Practice (GMP) standards while maintaining biosafety level 3 (BSL-3) requirements. Since facilities providing the necessary complex ventilation systems to meet both requirements are rare, we here describe a possibility to reproducibly propagate SARS-CoV-2 in the automated, closed cell culture device CliniMACS Prodigy® in a common BSL-3 laboratory. In this proof-of-concept study, we observed an approximately 300-fold amplification of SARS-CoV-2 under serum-free conditions with high lot-to-lot consistency in the infectious titers obtained. With the possibility to increase production capacity to up to 3000 doses per run, this study outlines a potential fast-track approach for the production of live-attenuated vaccine candidates based on highly pathogenic viruses under GMP-like conditions that may contribute to pandemic preparedness.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CliniMACS Prodigy®; GMP; human challenge study; live-attenuated vaccines; SARS-CoV-2; virus propagation